FROM HISTORY OF THE CRAFT OF THE FERGHANA VALLEY. (АT THE END OF XIX AND EARLY XX CENTURY) - Z. Esonov; A. Amanov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article deals with the history of the traditional craft of the rural population of the Ferghana valley at the end of XIX and early XX century.